Social Justice in Community Environments: A Collaborative Photovoice Process - Jennifer Schindler-Ruwisch; Helen Ramos Paiz; Kaila Pryor (Journal of Participatory Research Methods)
A small New England University and a local community center undertook a community based participatory research approach to understand the community-driven factors that most impact health. Photovoice was utilized to collaboratively highlight priority issues and to collectively advocate for change. The Photovoice approach was particularly useful in this context to transcend language differences and foster community dialogue between community and institutional partners in a way that dismantled traditional --- and historically harmful --- power dynamics between institutions and communities. The goal of utilizing this participatory-based method was to support community-identified social-ecological change, advocate for identified environmental justice priority issues, and support sustained community involvement. The novel aspects of the approach included guiding students and community members through this process in a community-engaged learning context that brought together linguistically diverse populations with a foundation of cultural humility, respect, and multi-directional learning.